Pengaruh Kompetensi Terhadap Peningkatan Kinerja Pegawai di Kementerian Agama Kabupaten Karawang - Sopiyah, Siti; Solehudin, Solehudin (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to determine the effect of employee competence on the performance of employees of the Ministry of Religion Karawang District . This type of research is quantitative research with descriptive and verification research methods . The sample in this study was 313. The sampling technique used in this study was saturated sampling. The analysis model in this study uses a multiple linear regression analysis model. The results of the study show that there is an influence between competence on the performance of employees of the Ministry of Religion of Karawang Regency Keywords: Competency, Employee Performance